The Effect of Using Instagram Polling Quiz Towards Students’ Vocabulary Mastery - Siska, Fransiska Feramaita (Ruang Publikasi Ilmiah, 2024)
The aims of this research is to determine the significant effect of using the Instagram Polling Quiz application on students' vocabulary mastery. To help enhance the students’ vocabulary mastery of tenth grade at SMKN 1 Trenggalek. This research uses a quantitative design method with a quasi-experimental method that uses statistical analysis. This research involved tenth grade of DKV 1 students and tenth grade of DKV 3 students at SMKN 1 Trenggalek in the academic year of 2023/2024 as subjects. In collecting data, researchers used multiple choice tests as instruments. The analysis provided is a pre-test and post-test after treatment. The researcher analyzed the data obtained utilizing SPSS version 25 with paired sample t-test analysis. Furthermore the post-test score in the experimental class was higher than the control class (79,03 > 74,83). So that the results of the paired sample t-test for experimental class in this research show a significance value of 0,000 < 0,05. This means that is rejected and is accepted. In conclusion, this research has been able to answer the research problem, namely “Is there any significant effect of utilizing Instagram Polling Quiz application towards students’ vocabulary mastery at the Tenth Grade of SMKN 1 Trenggalek?” Furthermore, there is a significant influence of implementing the Instagram Polling Quiz on students' vocabulary mastery.